2014
DOI: 10.1186/1472-6890-14-30
|View full text |Cite
|
Sign up to set email alerts
|

A simple and cost-effective method of DNA extraction from small formalin-fixed paraffin-embedded tissue for molecular oncologic testing

Abstract: BackgroundExtraction of DNA from formalin-fixed, paraffin-embedded (FFPE) tissue is a critical step in molecular oncologic testing. As molecular oncology testing becomes more important for prognostic and therapeutic decision making and tissue specimens become smaller due to earlier detection of suspicious lesions and the use of fine needle aspiration methods for tissue collection, it becomes more challenging for the typical molecular pathology laboratory to obtain reliable test results. We developed a DNA extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Thus, a Pinpoint solution can be used to minimize potential contamination from tissue flakes in the work area (Snow et al 2014). In the present study, we prevented flaking by adding lysis buffer directly onto the section prior to scraping.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a Pinpoint solution can be used to minimize potential contamination from tissue flakes in the work area (Snow et al 2014). In the present study, we prevented flaking by adding lysis buffer directly onto the section prior to scraping.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme acts on proteins by cleaving the peptide bonds adjacent to the carboxyl group of hydrophobic amino acid residues (aliphatic and aromatic). The optimal temperature for proteinase K is known to be between 50-60°C and the specific activity of proteinase K is enhanced by increasing the temperature from 52°C to 56°C (Snow et al, 2014). This will unfold the proteins, exposing the hydrophobic amino acid residues that would be normally encrypted inside the hydrophobic core of the protein making it easier for enzyme action.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the normal colonic mucosa archival tissue is a smaller biopsy compared to colorectal cancer archival tissue we were able to isolate good quality and quantity of DNA. Snow et al (2014) have reported that extraction of DNA from cellular tumors with a solid growth pattern and less contaminating nonneoplastic tissue is comparatively easy. In contrast to small biopsies which usually contain minute nests of tumor cells surrounded by non-tumor tissue creating a challenge in obtaining adequate quantity of DNA material (Snow et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the preanalytical steps are important to consider: the manual macrodissection of selected tumour areas has become a standard procedure in molecular pathology and is a powerful tool to reduce false negative results resulting from wild-type contamination ( 10 ). Selecting the right tumour area influences not only the result of the analysis, but also the allele frequency, the value of which is pivotal when reporting diagnostic findings ( 11 ).…”
Section: Introductionmentioning
confidence: 99%